Clear Skies : Cambodia Economic Update, October 2014 - World Bank Group (Washington, DC, 2014)
This issue of the Cambodia economic update covers the following selected issues: 1) making the most of the Cambodian rise sector; and 2) creating opportunities for firms as reflected in findings from the investment climate assessment. For FY2014 economic growth held up well despite domestic uncertainty and instability in neighboring countries. Real growth is estimated to reach 7.2 percent, driven by the garment, construction, and services sectors. Overall macroeconomic management has been good with fiscal consolidation underpinned by improved revenue administration. In 2015 with the expectation of renewed confidence and the return of political stability after ending a yearlong political deadlock in July 2014, bolstered by a strengthening global economy, Cambodia's real growth rate is expected to reach 7.5 percent, similar to that of 2013. The downside risks to the projected robust growth are a potential recurrence of labor unrest, natural disasters, especially the possibility of heavy floods, as well as regional political uncertainty. Concerning rice production, growth decelerated in 2013 highlighting the importance of revitalizing the rice sector so it becomes once again a key engine of GDP growth. While the milled-rice export market is steadily expanding and increasing the number of destination markets, the milling and transport costs of Cambodian rice make it loose the competitiveness it has at farm gate prices. The Royal Government of Cambodia (RGC) has set a very legitimate target of one million tons of milled rice exports that matters tremendously for poverty reduction and shared prosperity. Concerning the investment climate assessment findings, RGC's new five-year Rectangular Strategy III continues to prioritize improving the business environment to help diversify and increase value-added in production. The current period of robust growth represents an opportunity to make improvements to the business environment that will attract long-term investors. Proposed next steps in reforming the business environment include: a) addressing the high cost of electricity; b) automating government processes; c) encouraging new investment, particularly in special economic zones; d) continuing improvements to trade facilitation; e) completing the draft Competition Law; f) designing and implementing a system of incentives for business registration; and g) focusing on implementation and enforcement.